Measures of inflation and its impact on Indian Economy - T POTE, RAMESH; S KATTI, MEDHAVINI (International Journal of Psychosocial Rehabilitation, 2024)
Inflation is one of the economic parameter to be associated with the hike of price, it has its long and far reachingeffects on the society and social concerns. Inflation is a sustained increase in the general price level of goods andservices in an economy over a period of time. When the price level rises, each unit of currency buys fewer goods andservices. Consequently, Inflation reflects a reaction in one purchasing power per unit of money. Fluctuations inprices create an atmosphere of uncertainty which is not conducive to development activity. So inflations meanpaying more for goods than paying earlier. Not only essential goods see a hike, non-essential items like cigarettesetc. would also cost more. The price of everything goes up over time. The present article made an attempt to studythe impact of inflation on the economy, and measures of inflation in India. So in respect of obtaining a better view ofthe effects and influence of inflation on the society we need to take mainly the experience of poor and developingnations. This paper analyses the effects of inflation on our country’s economy that emerged in the recent past.